Titratable Avidity Reduction Enhances Affinity Discrimination in Mammalian Cellular Selections of Yeast-Displayed Ligands - Stern, Lawrence A. (ACS Comb Sci, 2017)
Yeast surface display selections against mammalian cell monolayers have proven effective in isolating proteins with novel binding activity. Recent advances in this technique allow for recovery of clones with even micromolar binding affinity. However, no efficient method has been shown for affinity based selection in this context. This study demonstrates the effectiveness of titratable avidity reduction using dithiothreitol (DTT) to achieve this goal. A series of epidermal growth factor receptor binding fibronectin domains with a range of affinities are used to quantitatively identify the number of ligands per yeast cell that yield the strongest selectivity between strong, moderate, and weak affinities. Notably, reduction of ligand display to 3,000 – 6,000 ligands per yeast cell yields 16-fold selectivity of a 2 nM binder relative to a 17 nM binder. These lessons are applied to affinity maturation of an EpCAM-binding fibronectin population, yielding an enriched pool of ligands with significantly stronger affinity than an analogous pool sorted by standard cellular selection methods. Collectively, this study offers a facile approach for affinity selection of yeast displayed ligands against full length cellular targets and demonstrates the effectiveness of this method by generating EpCAM-binding ligands that are promising for further applications.